Intracellular Molecular Differences in Aldosterone- Compared to Cortisol-Secreting Adrenal Cortical Adenomas - Seidel, Eric; Scholl, Ute I. (Frontiers in Endocrinology, 2016)
The adrenal cortex is a major site of steroid hormone production. Two hormones are of particular importance: aldosterone, which is produced in the zona glomerulosa in response to volume depletion and hyperkalemia, and cortisol, which is produced in the zona fasciculata in response to stress. In both cases, acute stimulation leads to increased hormone production, and chronic stimulation causes hyperplasia of the respective zone. Aldosterone- and cortisol-producing adenomas (APAs and CPAs) are benign tumors of the adrenal cortex that cause excess hormone production, leading to primary aldosteronism and Cushing’s syndrome, respectively. About 40% of APAs carry somatic heterozygous gain-of-function mutations in the K+ channel KCNJ5. These mutations lead to sodium permeability, depolarization, activation of voltage-gated Ca2+ channels and Ca2+ influx. Mutations in the Na+/K+-ATPase subunit ATP1A1 and the plasma membrane Ca2+-ATPase ATP2B3 similarly cause Na+ or H+ permeability and depolarization, whereas mutations in the Ca2+ channel CACNA1D directly lead to increased calcium influx. One in three CPAs carries a recurrent gain-of-function mutation (L206R) in the PRKACA gene, encoding the catalytic subunit of PKA. This mutation causes constitutive PKA activity by abolishing the binding of the inhibitory regulatory subunit to the catalytic subunit. These mutations activate pathways that are relatively specific to the respective cell type (glomerulosa versus fasciculata), and there is little overlap in mutation spectrum between APAs and CPAs, but co-secretion of both hormones can occur. Mutations in CTNNB1 (beta-catenin) and GNAS (Gsα) are exceptions as they can cause both APAs and CPAs through pathways that are incompletely understood.